Rośliny tatrzańskie w piśmiennictwie Zofii Radwańskiej-Paryskiej - Maciej Mączyński (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2015)
Basing on the texts by Zofia Radwańska-Paryska, the author reconstructs the ways of describing plants growing in the Tatra Mountains. The method of looking at the plant includes four different author’s points of view, mixed with each other, and the genre of the text does not determine the language used in it. The article reproduces four examples of linguistic images of plants.